2020
DOI: 10.3390/pharmaceutics12121222
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophils and Macrophages as Targets for Development of Nanotherapeutics in Inflammatory Diseases

Abstract: Neutrophils and macrophages are major components of innate systems, playing central roles in inflammation responses to infections and tissue injury. If they are out of control, inflammation responses can cause the pathogenesis of a wide range of diseases, such as inflammatory disorders and autoimmune diseases. Precisely regulating the functions of neutrophils and macrophages in vivo is a potential strategy to develop immunotherapies to treat inflammatory diseases. Advances in nanotechnology have enabled us to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(48 citation statements)
references
References 195 publications
(222 reference statements)
0
48
0
Order By: Relevance
“…Herein, nanotherapeutics and regenerative nanomedicines for inflammatory diseases and infection are advanced form of therapeutics that can govern cellular processes and triggered the routes of regeneration and initiate the route of healing of the damaged tissues, muscles, injuries, wounds including inflammation of various diseases and promote regeneration and cure infections noteworthy. [16] In the end, author believe that a proper elucidation of routes of infections, inflammation, immunity, immunity response and inflammatory injury will be a key approach to explore biological fight between immune defence and infecting agents. Outputs of these research interpretation and analysis will be definitely successful in the identification of the therapeutic targets.…”
Section: Globalize Your Researchmentioning
confidence: 99%
“…Herein, nanotherapeutics and regenerative nanomedicines for inflammatory diseases and infection are advanced form of therapeutics that can govern cellular processes and triggered the routes of regeneration and initiate the route of healing of the damaged tissues, muscles, injuries, wounds including inflammation of various diseases and promote regeneration and cure infections noteworthy. [16] In the end, author believe that a proper elucidation of routes of infections, inflammation, immunity, immunity response and inflammatory injury will be a key approach to explore biological fight between immune defence and infecting agents. Outputs of these research interpretation and analysis will be definitely successful in the identification of the therapeutic targets.…”
Section: Globalize Your Researchmentioning
confidence: 99%
“…Together with certain macrophage-residents of tissues that maintain their pool without the active participation of blood monocytes, macrophages derived from monocytes are involved in the inflammatory process. As a response to specifically occurring molecular patterns linked with pathogens and damage (PAMPs (pathogen-associated molecular patterns) and DAMPs (damage-associated molecular pattern), and host inherited signaling molecules, macrophages adopt a variety of functional phenotypes [ 11 ]. There are two opposite phenotypic states which are represented by the classical model of macrophage polarization: (1) the “classic” proinflammatory macrophage M1, generated by bacterial lipopolysaccharide (LPS) and/or gamma interferon (IFN-ɣ), (2) and the “alternative” anti-inflammatory macrophage M2, which may be stimulated by interleukin 4 (IL4) [ 12 ].…”
Section: Inflammatory Role Of Monocytesmentioning
confidence: 99%
“…In vivo studies provide a mechanistic understanding of how NΦs can help to increase the concentration of NPs in the target tissue. So far, the efficacy of NΦ-based drug delivery has been proved for curing inflammation, [144][145][146][147][148][149] stroke, [150] rheumatoid arthritis, [45] and cancer. [148,149,[151][152][153][154][155][156][157][158][159][160] Chu et al have shown that circulating NΦs preconditioned by activating stimuli are able to uptake intravenously (i.v.)…”
Section: Mechanisms Of Neutrophil-associated Nanoparticles Delivery: Hitchhiking Cell Following Cell or Mimicking Cellmentioning
confidence: 99%